Locality in national and global perspectives: An agenda for research - Abdullah, Irwan; Fernando, Henky (IAS Journal of Localities, 2023)
Prior to 1966, Indonesia was regarded as a country with an outdated order system. After the establishment of a new social order characterized by the incorporation of markets into people's lives, this period came to an end. The market's integration into society has transformed traditional self-sufficiency through subsistence production practices into a market-oriented and centralized modern society oriented toward the market. Various local beliefs, values, and practices have been supplanted with new ones as a result of the modern nation's formation. The national language, which functions as a measure of nationalism, has become a central factor that has transformed and threatened local languages. As a result, the influence of local languages has diminished significantly as urbanization, the offspring of welfare programs, has increased. National legal policies are enforced despite coexisting with customary laws, demonstrating modernization's dominance over marginalized local cultures. Under the guise of "progress," the new lifestyle is a component of the modernization project that not only shapes a new social practice but also disorients values and adds new hues to the system of ideas, values, and social practices that serve as the basis for societal development.